Single-cell transcriptome analysis of medaka lymphocytes reveals absence of fully mature T cells in the thymus and the T-lineage commitment in the kidney - Sakaguchi, Hiyori; Matsuda, Masaru; Iwanami, Norimasa (Frontiers in Immunology, 2025)
The cellular and molecular mechanisms underlying lymphocyte development are diverse among teleost species. Although recent scRNA-seq analyses of zebrafish hematopoietic cells have advanced our understanding of teleost hematopoiesis, comparative studies using another genetic model, medaka, which is evolutionarily distant among teleosts, is useful for understanding commonality and species-specificity in teleosts. In order to gain insight into how different molecular and cellular mechanisms of lymphocyte development in medaka and zebrafish, we established a recombination activating gene 1 (rag1) mutant medaka, which exhibited defects in V(D)J rearrangement of lymphocyte antigen receptor genes, accordingly lacking mature B and T cells. scRNA-seq analysis of wild type and rag1 mutant lymphocytes in the thymus and kidney characterized the developing stages of T and B cells, and found that most developed cd4+cd8– and cd4–cd8+ single-positive (SP) T-cell populations are absent in the thymus, and identified lymphoid progenitor cells already committed to the T lineage in kidney, implying unique features of medaka lymphocyte development.